In situ study of live specimens in an environmental scanning electron microscope - Tihlaříková, Eva; Neděla, Vilém; Shiojiri, Makoto (Microscopy and microanalysis, 2013)
In this paper we introduce new methodology for the observation of living biological samples in an environmental scanning electron microscope (ESEM). The methodology is based on an unconventional initiation procedure for ESEM chamber pumping, free from purge-flood cycles, and on the ability to control thermodynamic processes close to the sample. The gradual and gentle change of the working environment from air to water vapor enables the study of not only living samples in dynamic in situ experiments and their manifestation of life (sample walking) but also its experimentally stimulated physiological reactions. Moreover, Monte Carlo simulations of primary electron beam energy losses in a water layer on the sample surface were studied; consequently, the influence of the water thickness on radiation, temperature, or chemical damage of the sample was considered.
Keywords: mikrobiologie životního prostředí; Monte Carlo Method; metoda Monte Carlo; Water; Microscopy, Electron, Scanning; Environmental Microbiology; mikroskopie elektronová rastrovací; voda